(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
Diospyros udaiyanii, a new species from Kakkayam forest of Malabar Wildlife Sanctuary, Western Ghats of Kerala, India is described and illustrated. It is closely allied to D. pilosiusculata G. Don. in its stunted habit, smaller, glabrous leaves and large broad 4 or 5 glabrous calyx lobes with long pedicel, the absence of tomentose hairs on twigs, petiole, pedicel, calyx and leaf margin. Bangladesh J. Plant Taxon. 22(2): 83-86, 2015 (December)